Polybrominated Diphenyl Ethers, Polychlorinated Biphenyls, and Persistent Pesticides in Serum from the National Health and Nutrition Examination Survey: 2003–2008 - Sjödin, Andreas; Jones, Richard S; Caudill, Samuel P; Wong, Lee-Yang; Turner, Wayman E; Calafat, Antonia M (Environmental science & technology, 2014)
Polybrominated diphenyl ethers (PBDEs), polychlorinated biphenyls (PCBs), and persistent pesticides have been measured in pooled samples representative of the general noninstitutionalized population of the United States. The pools were made from individual sera from the National Health and Nutrition Examination Survey (NHANES) during 2005/06 and 2007/08. The pooled concentrations have been contrasted to NHANES 2003/04 individual measurements to evaluate changes in concentration over time and within survey period differences among age groups, race/ethnicity groups (Mexican American, non-Hispanic Black, non-Hispanic White), and sex. The arithmetic mean serum concentrations of several PCB congeners decreased from NHANES 2003/04 through 2007/08. Larger percentage reductions were seen for younger subjects (12–19 years) compared with older subjects (≥60 years). For example, the arithmetic mean concentration of 2,2′,4,4′,5,5′-hexachlorobiphenyl (PCB-153) was 36% lower in 12–19 year old adolescents when comparing NHANES 2007/08 with 2003/04; while for subjects over the age of 60 a 14% lower concentration was seen, although, the 95% confidence intervals overlapped. Similarly, the arithmetic mean serum concentrations of tri- to hexaBDEs were lower in NHANES 2007/08 than in 2003/04; however, most confidence intervals of the arithmetic means overlapped. These findings suggest that a reduction in PBDE serum concentrations cannot yet be detected following the discontinuation of pentaBDE in 2004.